Involvement of G‐CSF, IL‐6, and cortisol in transient neutrophilia after marathon races. (3rd September 2021) - Ueda, Naho; Musashi, Manabu; Shimoda, Taeko; Kawaguchi, Yuichi; Ohkubo, Iwao; Nakagawa, Yukie
Abstract: Objectives: The aim of this study was to clarify the mechanisms of the transient increase in neutrophils after running standard marathon races by measurement of cytokines involved in the production and survival of neutrophils, and cortisol. Methods: Fourteen male runners who participated in the Hokkaido Marathon, which is the sole marathon race held in summer in Japan, and finished the standard marathon were analyzed sequentially from the start until a maximum of 8 days after the finish. Results: Neutrophilia was observed in all runners just after they reached the goal (mean neutrophils: 13 226/μL). IL‐6, G‐CSF, and cortisol, but not GM‐CSF, increased at the same time. Time‐course studies with complete blood counts, biochemical markers, cytokines, and cortisol showed transient increases in neutrophils, monocytes, myoglobin, high‐sensitivity C‐reactive protein (hsCRP), G‐CSF, IL‐6, and cortisol. The increase in hsCRP was delayed 6 hours from the first increase in neutrophils. Correlations were observed between the neutrophil count and G‐CSF, IL‐6, and cortisol (G‐CSF; r = .667, IL‐6; r = .667, cortisol; r = .623). Conclusion: These results suggest that G‐CSF is directly involved, and IL‐6 is involved via cortisol in the transient neutrophilia that occurs after marathon races.